2011
DOI: 10.3945/jn.111.142299
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Bitter Melon to Rats Fed a High-Fructose Diet During Gestation and Lactation Ameliorates Fructose-Induced Dyslipidemia and Hepatic Oxidative Stress in Male Offspring

Abstract: This study examined the impact of maternal high-fructose intake and if metabolic control in the offspring could benefit from supplementing bioactive food components such as bitter melon (BM) to the maternal diet. In Expt. 1, virgin female rats received control (C), high-fructose (F; 60%), or BM-supplemented fructose (FBM; 1%) diet before conception until d 21 of lactation. Weaned male offspring were fed the C diet for 11 wk, forming C/C, F/C, and FBM/C groups. The F/C group had elevated serum insulin, TG, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 55 publications
3
43
1
Order By: Relevance
“…Although the HF-diet-fed offspring born to HF-diet-fed dams (HF/HF) were not significantly heavier compared with those from LF-diet-fed dams (LF/HF) at week 13, the former did exhibit significantly higher serum and muscle TG concentration, lower serum adiponectin concentration and 28% more visceral fat mass (Table 3). These results are in keeping with those from our laboratory [26] as well as those others [27,28] in that not all phenotypic features in the offspring derived from the two-generation exposure model would worsen compared with those from one-generation exposure. However, the similar metabolic profiles observed between dams and offspring lend support to the notion of programming effects of maternal HF diet.…”
Section: Discussionsupporting
confidence: 93%
“…Although the HF-diet-fed offspring born to HF-diet-fed dams (HF/HF) were not significantly heavier compared with those from LF-diet-fed dams (LF/HF) at week 13, the former did exhibit significantly higher serum and muscle TG concentration, lower serum adiponectin concentration and 28% more visceral fat mass (Table 3). These results are in keeping with those from our laboratory [26] as well as those others [27,28] in that not all phenotypic features in the offspring derived from the two-generation exposure model would worsen compared with those from one-generation exposure. However, the similar metabolic profiles observed between dams and offspring lend support to the notion of programming effects of maternal HF diet.…”
Section: Discussionsupporting
confidence: 93%
“…In consistent with our previous study showing that sEH (encoding Ephx2 gene) activity is induced by maternal HF exposure in offspring at 3 months of age [11], we observed that sEH protein level and its activity are higher in HF group compared to control in the 3-week-old kidney. Given that increased expression/activity of sEH and increased urine 14,15-DHET level have been associated with hypertension [18], our results indicated that HF-induced programmed hypertension, at least in part, may be related to activation of sEH. However, sEH was not altered in 1-day-old offspring, indicating that this process is likely to be a secondary phenomenon.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, fructose intake during gestation has been shown to cause changes in glucose metabolism, 10, 11, 31 and lipid metabolism, 10, 32, 33 as well as decreased fetal leptin signaling 34 in the offspring. Several of the studies mentioned above also reported a fructose-induced decrease in birth weight, 10, 11 whereas others including the present study (Table 2) did not see this effect.…”
Section: Discussionmentioning
confidence: 99%